Assessing Principle Characteristics of Family Travel (illustrated by the city of Sevastopol) - T. B. Melnikova; I. A. Shevchuk (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses in detail travel preferences and identifies characteristics of family groups. The methodological basis of the research is formed by empiric methods in the form of arranging and processing the formalized interview with closed questions. Sample survey was conducted on the territory of Sevastopol in July 2019 and 2020. Methodology of the research is based on studying families with children and tourists arriving to relatives and friends as key types of family travel groups. Families with children make up 42% of the tourist flow and 37% of the volume of one-day visitors; tourists coming to relatives and friend – 43% of the tourist flow. According to findings of the research family travel groups possess an individual profile, which is shown in somewhat different structure of cultural events, preferences in accommodation, geography and transportation. Such groups are mainly influenced by force-majeure circumstances therefore COVID-19 pandemic cut the share of these tourists on the territory of Sevastopol. In summer 2019 the duration of family group rest lasted, on average, 9.7 days and expense volume on the territory of Sevastopol made up 88 029 rubles, in 2020 the duration dropped to 9.4 days, however expenses reduced to 67 053 rubles. At the same time expenses of tourists without children dropped by 1 062 rubles. Social and economic contribution of family travel groups fosters the development of a wider set of industries in regional economy.